Digital Photocolorimetric Analysis of In Vitro Tooth Color Changes - Bezerra, A. P.; Oshima, S.; Feldmann, A.; Tango, R. N. [UNESP]; Duque, T. M.; Philippi, A. G.; Gonçalves, Tmsv (Operative Dentistry, 2024)
OBJECTIVE: Tooth color matching is challenging, and digital photocolorimetry using eLABor_aid (eLAB) provides objective evaluation through polarized photographs. However, its comparability with spectrophotometry remains unclear. METHODS AND MATERIALS: Bovine incisor root canals (n=30) were prepared to simulate an incomplete root apex. The teeth were randomly assigned to three groups based on intracanal medication: control (without medication); calcium hydroxide/propylene glycol; and triple-antibiotic paste (n=10 each). Tooth color was assessed using both eLAB and spectrophotometry. Measurements were taken at the crown medio-cervical region on five-time intervals (baseline, 1, 3, 7, and 14 days). Statistical analysis included two-way repeated-measures ANOVA, Sidak post hoc and Pearson's correlation test (α=0.05). RESULTS: No significant differences were observed between the two methods for either medication or follow-ups (p>0.05). Triple-antibiotic paste exhibited higher color variation (p<0.05). After 7 days, all groups presented significant color changes (p<0.05). Moderate to high correlations (R2 from 0.51 to 0.84, p<0.0001) were found between both methods for all groups at all intervals. CONCLUSION: The eLAB is a reliable method for detecting tooth color changes, and its results are comparable to spectrophotometry analysis.